2016
DOI: 10.1080/14737140.2016.1247699
|View full text |Cite
|
Sign up to set email alerts
|

Serous tubal intraepithelial carcinoma (STIC) – clinical impact and management

Abstract: Serous tubal intraepithelial carcinoma (STIC) is most likely precursor lesion of the most part of high-grade serous pelvis carcinomas, carcinosarcoma and undifferentiated carcinoma with incidence of 0.6% to 7% in BRCA carriers or women with strong family history of breast or ovarian carcinoma. STIC is a pathomorphologically and immunohistochemically detectable lesion which biological significance and clinical relevance is unknown. Areas covered: We investigate methods of STIC diagnostics and we present an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 69 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Wethington et al [23] also looked at the outcome of 12 BRCA carriers diagnosed with isolated STICs and found no difference in recurrence rate after staging or no treatment. Along with other authors [23, 28, 29] they concluded that this subgroup of patients with isolated STIC diagnosed at the time of RRSO should be offered long term follow up that could include CA 125 testing, but did not comment on the extent of surveillance.…”
Section: Discussionmentioning
confidence: 98%
“…Wethington et al [23] also looked at the outcome of 12 BRCA carriers diagnosed with isolated STICs and found no difference in recurrence rate after staging or no treatment. Along with other authors [23, 28, 29] they concluded that this subgroup of patients with isolated STIC diagnosed at the time of RRSO should be offered long term follow up that could include CA 125 testing, but did not comment on the extent of surveillance.…”
Section: Discussionmentioning
confidence: 98%
“…The last is STIC, which is characterized by the presence of a discrete lesion, single or multiple, and located in the fimbriated end of the tube. STIC lesions display epithelial stratification and mitotic figures, demonstrating atypical histologic changes (13,19). The epithelium of STIC showed strong p53 positivity and harbors clonal TP53 mutations (12).…”
Section: Histopathology Of Precursor Lesionsmentioning
confidence: 99%
“…A literature review through 2016 identified 103 reported cases of isolated STIC [19], mostly found in the context of RRS for BRCA1/2 mutation. Suggested management of STIC ranges from observation to performance of surgical staging and treatment [20, 21]. In a small clinical series, positive peritoneal cytology was reported among 12% of patients with isolated STIC and cases have been described in which surgical staging prompted by detection of STIC led to identification of occult cancer (reviewed in [19]).…”
Section: Discussionmentioning
confidence: 99%